Translating Cultures Unveiling the Art of Uzbek Literary Transformations - Nilufar Abdukhafizovna Khalimova (Indonesian Journal of Cultural and Community Development, 2024)
This study conducts a linguocultural analysis of 20th-century Uzbek literary translations, illuminating the complex interaction between language and culture, particularly in the nuanced translation of stories like "Shum bola" into "A Naughty Boy." Existing research often overlooks the depth of cultural understanding required for effective literary translation, a gap this study addresses by highlighting the challenges and strategies in preserving the original texts' emotional and cultural essence. Employing an integrated approach of linguistic, cultural, and sociological methods, the research examines several translations to demonstrate how cultural context significantly impacts the translation process. Results underscore the necessity for translators to have a profound comprehension of both source and target cultures to ensure meaningful translations. The findings advocate for enhanced translator training in cultural competencies, contributing to the fields of translation studies and intercultural communication. Highlights: Intricate Relationship: Emphasizes the complex interplay between language and culture in translation. Cultural Knowledge: Highlights the essential role of deep cultural understanding for effective translation. Methodological Approach: Utilizes an integrated linguistic, cultural, and sociological framework to explore translation challenges. Keywords: Linguocultural Analysis, Translation Studies, Cultural Context, Literary Translation